Odpowiedzi

2010-01-25T17:39:12+01:00

1.x=-2-2y

2*(-2-2y)-y=1
-4-4y-y=1
-5y=1+4
-5y=5|/-5
y= -1

2x –(-1)=1
2x+1=1
2x=1-1
2x=0 |/2
x= 0

2.
3x-2y=-12 |-2
2x-5y=-19 | 3

-6x+4y=24
6x-5y=-57
-y=-33 |/-1
y=33

3x-2y=-12
3x -66=-12
3x=-54 |/3
x= 18



3.
3(x-y)+4x=8
3(x-5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

3x-3y+4x=8
3x-15y +9y=5

7x-3y=8 |-2
3x-6y=5

-14x +6y= -16
3x -6y= 5
-11x= -11 |/-1
x= 1

3x-6y=5
3-6y=5
-6y=5-3
-6y=2 |/-6
y= -1/3



2010-01-25T17:44:23+01:00
1. Metoda podstawiania :
x +2y=-2
2x-y=1

-y=1-2x
y=-1+2x

x+2(-1+2x)=-2
x-2+4x=-2
5x=0
x=0

y=-1-2*0
y=-1


2.Metoda przeciwnych współczynników :
3x-2y=-12|*(-5)
2x-5y=-19|*2

-15x+10y=60
4x-10y=-38
-11x=22
x=-2

3*(-2)-2y=-12
-2y=-6
y=3


3.Dowolna metoda :
3(x-y)+4x=8
3(x-5y)=5-9y

3x-3y+4x=8
3x-15y+9y=5

7x-3y=8|*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5
-11x=-11
x=1

7x-3y=8
7-3y=8
-3y=1
y=-1/3